The suitability of pavement types for children in urban park - Ahmad, Nur Farah; Zakariya, Khalilah (KAED, IIUM, 2016)
Recent studies have found that 68% of the children’s injuries occurred at the park is due to the fall to the surface. This happens due to the design of the surface of the park that did not meet the needs of the children. The aim of this study is to examine the suitability of common pavements used in the urban park for children through a case study in Shah Alam Lake Garden. The use of five types of pavements was observed and 30 questionnaire surveys were distributed among parents in Shah Alam Lake Garden to determine the most suitable pavements for children. The study found that among the five types of pavement, block pavers serve as the most suitable surface for the children. There are several factors that contribute to the selection of block pavers in terms of texture, colour and pattern. To further improve the suitability of the pavements for the children, this study suggest that the condition, colour and patterns of the selected pavement can be designed to fulfil the needs of the children’s activities.